Ziad ibn Abih Policy in Basra (45/665 A.D.), as Reflected in the book of (Al-Akhbar al-Mukhafiyat ) by Zubayr Ibn Bakkar, who died in 256-869 A.D - Fadil , Researcher. Yasmin; Ibrahim Mohamed, Assist. Prof. Dr. Moayad (Basra studies journal, 2023)
Ziyad bin Abihi is one of the most powerful governors or rulers who ruled Iraq. He used cruelty and violence since his arrival to Basra in order to establish the pillars of the Umayyad state. Ziyad bin Abihi worked to reduce the authority of the tribes in Basra and limit their influence and control. He also gave orders to his police chief to kill everyone who violated the rules of Ziyad bin Abih, and Ziyad struck all those who opposed the Umayyad state and worked to expel them from Iraq by forcibly displacing them to areas far from Iraq in order to impose the control of the state on the other opposed states to the Umayyad rule.